1992
DOI: 10.1084/jem.175.3.637
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor-mediated suppression of the interleukin 2 gene expression through impairment of the cooperativity between nuclear factor of activated T cells and AP-1 enhancer elements.

Abstract: SummaryThe immunosuppressant hormone dexamethasone (Dex) interferes with T cell-specific signals activating the enhancer sequences directing interleukin 2 (IL-2) transcription. We report that the Dex-dependent downregulation of 12-O-tetradecanoyl-phorbo1-13-acetate (TPA) and calcium ionophore-induced activity of the I1,2 enhancer are mediated by glucocorticoid receptor (GR) via a process that requires intact NH2-and COOH-terminal and DNA-binding domains. Functional analysis of chloramphenicol acetyltransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(88 citation statements)
references
References 56 publications
2
83
0
3
Order By: Relevance
“…40,42,43 Phosphorylated JUN as homodimer, or heterodimer with FOS, has potent AP-1 activity, regulating the expression of a number of genes, including c-jun itself 44 and cytokines. 45 We show here that incubation of the hepatocytes in the presence of both EGF and TNF-␣ clearly produced an activation of JNK, which was higher than that observed by each one of those factors acting independently (Fig. 3).…”
Section: Discussionmentioning
confidence: 78%
“…40,42,43 Phosphorylated JUN as homodimer, or heterodimer with FOS, has potent AP-1 activity, regulating the expression of a number of genes, including c-jun itself 44 and cytokines. 45 We show here that incubation of the hepatocytes in the presence of both EGF and TNF-␣ clearly produced an activation of JNK, which was higher than that observed by each one of those factors acting independently (Fig. 3).…”
Section: Discussionmentioning
confidence: 78%
“…Regulation of the IL-2 gene occurs through a cooperative mechanism involving NF-AT and AP-1 interaction at the promoter. Inhibition by glucocorticoids involves disruption of this cooperativity (69) through the GR binding to AP-1 that disrupts binding to NF-AT (70). NF-AT and AP-1 can bind to the CLE0 element in the GM-CSF promoter (15).…”
Section: Discussionmentioning
confidence: 99%
“…The role of steroid hormones in inducing secretion of different cytokines by Th lymphocytes is currently under examination. It has been reported that cortisol and pharmacological doses of glucocorticoids (GC) reduce the production of IL-1, which acts as a costimulator on T cell activation [34], and of the type 1 cytokines IL-2 and IFN- [35,36], impairing antigen-and mitogen-induced T lymphocyte proliferation [37]. Additionally, GC favour the production of type 2 cytokines by inhibiting the transcription of IL-2 and IFN-genes and by favouring the production of IL-4, thus stimulating Th2 cells, and suppressing Th1 cells [38,39].…”
Section: Discussionmentioning
confidence: 99%